UNWANTED AUTOPSIES: CAN THEY BE AVOIDED - Rastogi, Prateek; D Souza, Haneil Larson; Shetty H, Pavanchand (Journal of Forensic Medicine and Toxicology, 2025)
Autopsy or post mortem examination in medicolegal cases is a recommended procedure in order to conclude the cause of death, establish identification or to rule out foul play. It is routinely done in almost all medico-legal death cases but frequently few cases are encountered where on receiving the requisition, going through case history or hospital records autopsy surgeon is convinced that autopsy is unwanted or unnecessary in that case and will yield no additional information, still it needs to be done as investigating authority wants it to be done. In present paper 5 such cases are discussed where in spite of all circumstantial evidences, case records and related findings post mortem examination was ordered. This paper is an attempt to discuss the necessity as well as futility of ordering a post mortem as a routine in all medicolegal death cases.
Keywords: medico-legal case; post mortem; cause of death; autopsy